A method for preparing a ceramic-based brake pad
By introducing modified molybdenum disulfide and heat treatment technology into the preparation method of ceramic-based brake pads, the problems of unstable friction coefficient, poor wear and heat resistance of existing ceramic-based brake pads are solved, and higher chemical and thermal stability and better friction performance are achieved, and service life is extended.
Patent Information
- Application Number
- CN202411436870.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-10-15
AI Technical Summary
The friction coefficient of existing ceramic-based brake pads is unstable, has poor wear and heat resistance, and has a short service life.
A ceramic-based brake pad is adopted to obtain ceramic-based brake pads by weighing reinforced fibers, fillers, phenolic resin powder, nitrile rubber powder and modified molybdenum disulfide by weight, stirring and mixing, and undergoing heat treatment to obtain ceramic-based brake pads with improved chemical and thermal stability and frictional properties.
It significantly improves the chemical and thermal stability of ceramic-based brake pads, improves friction performance, and extends service life.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of brake pad preparation, in particular to a method for preparing a ceramic-based brake pad. Background Art
[0002] The brake pad of a car is a friction material. Its main function is to absorb kinetic energy through friction with metal to make the vehicle work safely and reliably. It should have good friction performance and wear resistance, as well as good mechanical strength and heat resistance. Ceramic-based brake pads have a stable friction coefficient, good thermal stability and good wear resistance. They do not contain metal components, and their service life is more than twice that of other brake pads. They have superior comprehensive performance and are a clean and environmentally friendly product.
[0003] Chinese patent CN108488280A: discloses a high-speed train ceramic-based brake pad composite material, whose components include Mn+1XAn series layered compounds, high entropy compounds, stainless steel fibers, stainless steel powders, graphite and molybdenum sulfide, and the mass percentages of the above materials are 40-70:15-35:5-15:5-20:0-4:0-4; the preparation method of the above ceramic-based brake pad composite material is mainly to uniformly mix the above powder and stainless steel fibers, and hot-press and sinter at 15-50MPa at 1100-1200°C under vacuum and argon environment conditions to obtain the high-speed train ceramic-based brake pad composite material.
[0004] Chinese patent CN112762119A: relates to the field of brake pad technology, and discloses a method for preparing a brake pad with good anti-thermal decay effect, comprising the following steps: S1, obtaining raw materials, 3-7 parts of resin, 2-3 parts of tire powder, 2-5 parts of friction powder, 13-15 parts of mixed fiber, 12-14 parts of lubricant, and 65-68 parts of filler; S2, taking out half of the raw materials obtained in S1 and putting them into a high-speed mixer for premixing, stirring at high speed to make the mixed fiber evenly dispersed; S3, putting the premixed raw materials and the remaining half of the materials into the high-speed mixer and stirring at high speed, and pouring them into a container for standby use.
[0005] Chinese patent CN111303584A: discloses a friction material for brake pads, a brake pad and a method for preparing a brake pad, wherein the components are mixed in the following proportions by mass: 30-40% modified phenolic resin, 8-13% nitrile rubber, 6-10% polyphenylene sulfide, 3-7% magnesium oxide, 5-7% aluminum oxide, 6-10% copper sulfide, 4-8% mica powder, 6-11% aramid fiber, 7-13% ceramic fiber, the magnesium oxide and aluminum oxide are used as friction enhancers, and the copper sulfide is used as a lubricant.
[0006] The brake pads prepared by the above patents and prior art have unstable friction coefficients, poor wear resistance, poor heat resistance and short service life. Summary of the invention
[0007] In order to solve the above problems, the present invention provides a method for preparing a ceramic-based brake pad, and the operating steps are as follows:
[0008] S1: Weigh 25-40 parts of reinforcing fiber, 10-30 parts of filler, 5-10 parts of phenolic resin powder, 1-5 parts of nitrile rubber powder, and 1-5 parts of modified molybdenum disulfide by weight, and stir and mix for 5-10 minutes;
[0009] S2: The mixed material is pressed into a shape, and after heat treatment, a ceramic-based brake pad is obtained.
[0010] Furthermore, the reinforcing fiber is one of carbon fiber, alumina fiber, aluminum silicate fiber and zirconium oxide fiber.
[0011] Furthermore, the filler is one of barite, expanded vermiculite, sepiolite, corundum, zircon, graphite, talc, wollastonite, zeolite, diatomaceous earth, brucite, and hydrotalcite-like.
[0012] Furthermore, the pressing pressure is 3-5Mpa, and the pressing time is 5-10min.
[0013] Furthermore, the heat treatment operation steps are: keeping warm at 130-140°C for 30-60min; keeping warm at 140-160°C for 30-60min; keeping warm at 160-180°C for 30-60min; keeping warm at 180-200°C for 90-120min; keeping warm at 200-210°C for 150-180min.
[0014] Furthermore, the preparation method of the modified molybdenum disulfide is:
[0015] A1: Add 100-150 parts by weight of molybdenum disulfide, 4-8 parts of γ-methacryloxypropyltrimethoxysilane, and 1000-1200 parts of dimethyl sulfone into a reaction kettle 1, and react at 40-50° C. for 10-14 hours;
[0016] A2: Add 10-20 parts of p-terphenyl-4,4'-dithiol and 3-9 parts of sodium methoxide, and react at 80-90°C for 100-150 minutes. This step and the subsequent step A4 are carried out under nitrogen protection;
[0017] A3: Add 2-5 parts of 10,13-epoxy-10,12-octadecadienoic acid, 4-8 parts of zirconium nitrate, and 100-120 parts of dimethyl sulfone to reaction kettle 2 by weight, and react at 30-40° C. for 5-10 hours to generate a 10,13-epoxy-10,12-octadecadienoic acid / zirconium complex;
[0018] A4: Add the product of reactor 2 into reactor 1, react at 80-90° C. for 100-150 minutes to obtain modified molybdenum disulfide.
[0019] Reaction mechanism
[0020] Molybdenum disulfide reacts with γ-methacryloxypropyltrimethoxysilane to obtain molybdenum disulfide containing acryloyloxy group; the molybdenum disulfide undergoes a thiol addition reaction with a thiol group of terphenyl-4,4'-dithiol; a 10,13-epoxy-10,12-octadecadienoic acid / zirconium complex undergoes a thiol addition reaction with a thiol group of terphenyl-4,4'-dithiol; and the modified molybdenum disulfide is obtained.
[0021] Technical Effects
[0022] The present invention provides a method for preparing a ceramic-based brake pad. Compared with the prior art, the present invention has the following significant effects:
[0023] 1. Enhance chemical and thermal stability:
[0024] The introduction of terphenyl and zirconium complexes not only brings chemical stability to molybdenum disulfide, but also provides higher thermal stability; this is because these macromolecular structures are not easily decomposed or deformed at high temperatures and can withstand thermal stress under extreme conditions without losing their structural integrity.
[0025] 2. Improve friction performance:
[0026] In brake pads, friction materials must be able to provide a stable and effective friction coefficient under various temperature and pressure conditions; the surface structure of modified MoS2 can better withstand repeated friction loads, and the benzene ring structure of terphenyl can interact with the layered structure of MoS2 to form a stable π-π stacking effect; this interaction enhances the bonding force between layers and prevents peeling or dispersion in chemical reactions; the electron cloud of each benzene ring can interact with the d orbital or p orbital of the Mo or S atom on the surface of MoS2, further improving the stability of the structure.
[0027] The introduction of terphenyl changes the electron density distribution on the surface of MoS2 and affects the electronic properties of the material; this effect helps to reduce the electron loss of MoS2 in chemical reactions and improve the overall chemical stability.
[0028] The large molecular volume of terphenyl forms an effective spatial barrier on the surface of molybdenum disulfide, blocking the approach of chemical substances that may cause MoS2 to decompose or oxidize; the steric hindrance effect of this large-sized molecule also provides a mechanical barrier for molybdenum disulfide to resist external physical impact or friction, further protecting the internal structure from damage; the smooth surface of modified molybdenum disulfide may reduce direct contact between materials and form a uniform friction film, thereby providing a smoother and more continuous friction output during braking. DETAILED DESCRIPTION
[0029] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description in combination with embodiments and comparative examples:
[0030] The friction coefficient, wear rate and thermal expansion rate were tested using an XD-MSM constant speed friction tester in accordance with GB / T 5763-2008. The results are recorded in Table 1.
[0031] Example 1
[0032] A method for preparing a ceramic-based brake pad, the operating steps of which are:
[0033] S1: Weigh 25g of reinforcing fiber, 10g of filler, 5g of phenolic resin powder, 1g of nitrile rubber powder, and 1g of modified molybdenum disulfide, and stir and mix for 5min;
[0034] S2: The mixed material is pressed into a shape, and after heat treatment, a ceramic-based brake pad is obtained.
[0035] The reinforcing fiber is carbon fiber.
[0036] The filler is barite.
[0037] The pressing pressure is 3Mpa and the pressing time is 5min.
[0038] The heat treatment operation steps are: keeping warm at 130°C for 30 minutes; keeping warm at 140°C for 30 minutes; keeping warm at 160°C for 30 minutes; keeping warm at 180°C for 90 minutes; and keeping warm at 200°C for 150 minutes.
[0039] The preparation method of the modified molybdenum disulfide is:
[0040] A1: 100 g of molybdenum disulfide, 4 g of γ-methacryloxypropyltrimethoxysilane and 1000 g of dimethyl sulfone were added to reactor 1 and reacted at 40° C. for 10 hours;
[0041] A2: Add 10 g of terphenyl-4,4'-dithiol and 3 g of sodium methoxide, and react at 80° C. for 100 minutes. This step and the subsequent step A4 are carried out under nitrogen protection;
[0042] A3: 2 g of 10,13-epoxy-10,12-octadecadienoic acid, 4 g of zirconium nitrate, and 100 g of dimethyl sulfone were added to reactor 2, and reacted at 30° C. for 5 hours to generate a 10,13-epoxy-10,12-octadecadienoic acid / zirconium complex;
[0043] A4: Add the product of reactor 2 into reactor 1, react at 80° C. for 100 minutes to obtain modified molybdenum disulfide.
[0044] Example 2
[0045] A method for preparing a ceramic-based brake pad, the operating steps of which are:
[0046] S1: Weigh 30g reinforcing fiber, 15g filler, 6g phenolic resin powder, 2g nitrile rubber powder, and 2g modified molybdenum disulfide, and stir and mix for 6min;
[0047] S2: The mixed material is pressed into a shape, and after heat treatment, a ceramic-based brake pad is obtained.
[0048] The reinforcing fiber is alumina fiber.
[0049] The filler is expanded vermiculite.
[0050] The pressing pressure is 4Mpa and the pressing time is 6min.
[0051] The heat treatment operation steps are: keeping warm at 135°C for 40 minutes; keeping warm at 145°C for 40 minutes; keeping warm at 165°C for 40 minutes; keeping warm at 185°C for 100 minutes; and keeping warm at 205°C for 160 minutes.
[0052] The preparation method of the modified molybdenum disulfide is:
[0053] A1: Add 110 g of molybdenum disulfide, 5 g of γ-methacryloxypropyltrimethoxysilane and 1050 g of dimethyl sulfone into reactor 1 and react at 45° C. for 11 hours;
[0054] A2: Add 13 g of p-terphenyl-4,4'-dithiol and 5 g of sodium methoxide, and react at 85° C. for 110 minutes. This step and the subsequent step A4 are carried out under nitrogen protection;
[0055] A3: 3 g of 10,13-epoxy-10,12-octadecadienoic acid, 5 g of zirconium nitrate, and 105 g of dimethyl sulfone were added to reactor 2, and reacted at 35° C. for 6 hours to generate a 10,13-epoxy-10,12-octadecadienoic acid / zirconium complex;
[0056] A4: The product of reactor 2 was added into reactor 1, and the mixture was reacted at 85° C. for 110 minutes to obtain modified molybdenum disulfide.
[0057] Example 3
[0058] A method for preparing a ceramic-based brake pad, the operating steps of which are:
[0059] S1: Weigh 35g of reinforcing fiber, 25g of filler, 8g of phenolic resin powder, 4g of nitrile rubber powder, and 4g of modified molybdenum disulfide, and stir and mix for 8min;
[0060] S2: The mixed material is pressed into a shape, and after heat treatment, a ceramic-based brake pad is obtained.
[0061] The reinforcing fiber is aluminum silicate fiber.
[0062] The filler is sepiolite.
[0063] The pressing pressure is 4Mpa and the pressing time is 8min.
[0064] The heat treatment operation steps are: keeping warm at 135°C for 50 minutes; keeping warm at 155°C for 50 minutes; keeping warm at 175°C for 50 minutes; keeping warm at 195°C for 110 minutes; and keeping warm at 205°C for 170 minutes.
[0065] The preparation method of the modified molybdenum disulfide is:
[0066] A1: 140 g of molybdenum disulfide, 7 g of γ-methacryloxypropyltrimethoxysilane and 1150 g of dimethyl sulfone were added to reactor 1 and reacted at 45° C. for 13 hours;
[0067] A2: Add 18 g of p-terphenyl-4,4'-dithiol and 3-9 g of sodium methoxide, and react at 85° C. for 140 minutes. This step and the subsequent step A4 are carried out under nitrogen protection;
[0068] A3: 4 g of 10,13-epoxy-10,12-octadecadienoic acid, 7 g of zirconium nitrate, and 115 g of dimethyl sulfone were added to reactor 2, and reacted at 35° C. for 8 hours to generate a 10,13-epoxy-10,12-octadecadienoic acid / zirconium complex;
[0069] A4: The product of reactor 2 was added into reactor 1, and the mixture was reacted at 85° C. for 140 minutes to obtain modified molybdenum disulfide.
[0070] Example 4
[0071] A method for preparing a ceramic-based brake pad, the operating steps of which are:
[0072] S1: Weigh 40g reinforcing fiber, 30g filler, 10g phenolic resin powder, 5g nitrile rubber powder, and 5g modified molybdenum disulfide, and stir and mix for 10min;
[0073] S2: The mixed material is pressed into a shape, and after heat treatment, a ceramic-based brake pad is obtained.
[0074] The reinforcing fiber is zirconium oxide fiber.
[0075] The filler is wollastonite.
[0076] The pressing pressure is 5Mpa and the pressing time is 10min.
[0077] The heat treatment operation steps are: keeping warm at 140°C for 60 minutes; keeping warm at 160°C for 60 minutes; keeping warm at 180°C for 60 minutes; keeping warm at 200°C for 120 minutes; and keeping warm at 210°C for 180 minutes.
[0078] The preparation method of the modified molybdenum disulfide is:
[0079] A1: 150 g of molybdenum disulfide, 8 g of γ-methacryloxypropyltrimethoxysilane and 1200 g of dimethyl sulfone were added to reactor 1 and reacted at 50° C. for 14 hours;
[0080] A2: Add 20 g of terphenyl-4,4'-dithiol and 9 g of sodium methoxide, and react at 90° C. for 150 minutes. This step and the subsequent step A4 are carried out under nitrogen protection;
[0081] A3: 5 g of 10,13-epoxy-10,12-octadecadienoic acid, 8 g of zirconium nitrate, and 120 g of dimethyl sulfone were added to reactor 2, and reacted at 40° C. for 10 hours to generate a 10,13-epoxy-10,12-octadecadienoic acid / zirconium complex;
[0082] A4: The product of reactor 2 was added into reactor 1, and the mixture was reacted at 90° C. for 150 minutes to obtain modified molybdenum disulfide.
[0083] Comparative Example 1
[0084] The molybdenum disulfide is not modified, and the other steps are the same as in Example 1.
[0085] Comparative Example 2
[0086] The γ-methacryloxypropyltrimethoxysilane was not added, and the other steps were the same as those in Example 1.
[0087] Comparative Example 3
[0088] The 10,13-epoxy-10,12-octadecadienoic acid / zirconium complex was not added, and the other steps were the same as in Example 1.
[0089] Table 1
[0090] Friction coefficient Wear rate / 10-7cm3 / N·m Thermal expansion rate / % Service life / km Example 1 0.41 0.19 1.3 106500 Example 2 0.43 0.17 1.1 108600 Example 3 0.45 0.15 0.9 109900 Example 4 0.46 0.13 0.8 110300 Comparative Example 1 0.33 0.43 2.5 58200 Comparative Example 2 0.35 0.26 1.7 85300 Comparative Example 3 0.36 0.23 1.6 91500
[0091] Through the data analysis of the above embodiments and comparative examples, the ceramic-based brake pad prepared by the present invention has stable friction performance, good high temperature resistance and long service life.
[0092] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a ceramic-based brake pad, the operating steps of which are: S1: Weigh 25-40 parts of reinforcing fiber, 10-30 parts of filler, 5-10 parts of phenolic resin powder, 1-5 parts of nitrile rubber powder, and 1-5 parts of modified molybdenum disulfide by weight, and stir and mix for 5-10 minutes; S2: Pressing the mixed material into a shape and subjecting it to heat treatment to obtain a ceramic-based brake pad; The preparation method of the modified molybdenum disulfide is: A 1: Add 100-150 parts by weight of molybdenum disulfide, 4-8 parts of γ-methacryloxypropyltrimethoxysilane, and 1000-1200 parts of dimethyl sulfone into a reaction kettle 1, and react at 40-50° C. for 10-14 hours; A2: Add 10-20 parts of p-terphenyl-4,4'-dithiol and 3-9 parts of sodium methoxide, and react at 80-90°C for 100-150 minutes. This step and the subsequent step A4 are carried out under nitrogen protection; A3: Add 2-5 parts of 10,13-epoxy-10,12-octadecadienoic acid, 4-8 parts of zirconium nitrate, and 100-120 parts of dimethyl sulfone to reaction kettle 2 by weight, and react at 30-40° C. for 5-10 hours to generate a 10,13-epoxy-10,12-octadecadienoic acid / zirconium complex; A4: Add the product of reactor 2 into reactor 1, react at 80-90° C. for 100-150 minutes to obtain modified molybdenum disulfide.
2. The method for preparing a ceramic-based brake pad according to claim 1, characterized in that: The reinforcing fiber is one of carbon fiber, alumina fiber, aluminum silicate fiber and zirconium oxide fiber.
3. The method for preparing a ceramic-based brake pad according to claim 1, characterized in that: The filler is one of barite, expanded vermiculite, sepiolite, corundum, zircon, graphite, talc, wollastonite, zeolite, diatomaceous earth, brucite and hydrotalcite.
4. The method for preparing a ceramic-based brake pad according to claim 1, characterized in that: The pressing pressure is 3-5Mpa and the pressing time is 5-10min.
5. The method for preparing a ceramic-based brake pad according to claim 1, characterized in that: The heat treatment operation steps are: 130-140°C for 30-60min; 140-160°C for 30-60min; 160-180°C for 30-60min; 180-200°C for 90-120min; Keep warm at 200-210℃ for 150-180min.
Citation Information
Patent Citations
High-speed train ceramic-base brake block composite material
CN108488280A
Friction material for brake pad, brake pad and preparation method of brake pad
CN111303584A
Preparation method of brake pad with good effect of resisting heat fading
CN112762119A
Preparation method of high-wear-resistance brake pad
CN118185093A
Copper-free ceramic friction material for brake pad and preparation method of copper-free ceramic friction material
CN118272048A